Rational design of nickel cobalt sulfide/cobalt sulfide sheet-on-sheet structure for asymmetric supercapacitors. (1st September 2018) - Cheng, Jia-Wen; Lin, Lu-Yin; Hong, Wei-Lun; Lin, Lu-Ying; Chen, Hong-Qin; Lai, He-Xin
Abstract: Nickel cobalt sulfide (Ni-Co-S) is one of the most potential electrocapacitive materials for energy storage devices, owing to the high electrical conductivity and multiple oxidation states. Large surface area and efficient charge/ion transfer routes are dispensable for an efficient electrocapacitive material. The rational-designed core/shell structures are fabricated in this work by first synthesizing the Ni-Co-S nanosheet array on the Ni foam using a hydrothermal reaction as the core and then depositing the cobalt sulfide (Co-S) nanosheets as the shell via electrodeposition. The electrodepositing cycles are varied to synthesize the Co-S shell with different sizes and densities. The highest specific capacitance (CF ) of 8.47 F/cm 2 corresponding to the capacity of 1.65 mAh/cm 2 are obtained at 5 mV/s for the optimized Ni-Co-S/Co-S electrode prepared using 40 cycles for electrodeposition, due to the larger surface area of the sheet-on-sheet structure and the suitable size of the gaps between nanosheets for efficient ions diffusion. A CF value of714.2 mF/cm 2 at 5 mA/cm 2, a potential window of 1.6 V, and a CF retention of 65% after 5000 cycles repeated charge/discharge process are achieved for an asymmetric supercapacitor assembled using the optimized Ni-Co-S/Co-S electrode as the positive electrode and an activated carbon electrode as the negative electrode. Graphical abstract: Image 1 Highlights: A Ni-Co-S/Co-S core/shell electrode is got via hydrothermal and electrodeposition. Electrodepositing cycle is varied to make Co-S shell with varied sizes/densities. A CF value of 8.47 F/cm 2 is got at 5 mV/s for an optimized Ni-Co-S/Co-S electrode. The electrode has large sheet-on-sheet surface area and suitable gaps in-between. A CF value of 714.2 mF/cm 2 is obtained for a resulting asymmetric supercapacitor.